Adjuvant Zoledronic Acid in High‐Risk Giant Cell Tumor of Bone: A Multicenter Randomized Phase II Trial. (30th April 2019) - Lipplaa, Astrid; Kroep, Judith R.; van der Heijden, Lizz; Jutte, Paul C.; Hogendoorn, Pancras C.W.; Dijkstra, Sander; Gelderblom, Hans
Abstract: Lessons Learned: Adjuvant treatment with zoledronic acid did not decrease the recurrence rate of giant cell tumor of bone (GCTB) in this study. The efficacy could not be determined because of the small sample size. GCTB recurrences, even in the denosumab era, are still an issue; therefore, a randomized study exploring the efficacy of zoledronic acid in the adjuvant setting in GCTB is still valid. Background: Bisphosphonates are assumed to inhibit giant cell tumor of bone (GCTB)‐associated osteoclast activity and have an apoptotic effect on the neoplastic mononuclear cell population. The primary objective of this study was to determine the 2‐year recurrence rate of high‐risk GCTB after adjuvant zoledronic acid versus standard care. Methods: In this multicenter randomized open‐label phase II trial, patients with high‐risk GCTB were included (December 2008 to October 2013). Recruitment was stopped because of low accrual after the introduction of denosumab. In the intervention group, patients received adjuvant zoledronic acid (4 mg) intravenously at 1, 2, 3, 6, 9, and 12 months after surgery. Results: Fourteen patients were included (intervention n = 8, controls n = 6). Median follow‐up was long: 93.5 months (range, 48–111). Overall 2‐year recurrence rate was 38% (3/8) in the intervention versus 17% (1/6) in the control group ( p = .58). All recurrences were seen within the first 15 months after surgery. Conclusion: Adjuvant treatment with zoledronic acid did not decrease the recurrence rate of GCTB in this study. The efficacy could not be determined because of the small sample size. Because recurrences, even in the denosumab era, are still an issue, a randomized study exploring the efficacy of zoledronic acid in the adjuvant setting in GCTB is still valid.